The relation between athletic sports and prevalence of amenorrhea and oligomenorrhea in Iranian female athletes - Dadgostar, H.; Razi, M.; Aleyasin, A.; Alenabi, T.; Dahaghin, S. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2009)
Background In 1992, the concept of female athlete triad was introduced to describe the interrelated problems of amenorrhea, eating disorders and osteoporosis seen in female athletes. To gain a clearer picture of amenorrhea/oligomenorrhea in Iran, one of the main components of the female athlete triad, we therefore established this study on the prevalence of amenorrhea/oligomenorrhea in elite Iranian female athletes, also evaluating the risk factors of these disorders in the same population.